Zwitterionic polyvinylidene fluoride membranes with strong underwater superoleophobicity and oil-fouling resistance for oily water purification. Issue 3 (June 2022) - Yang, Yu-Ling; Li, Man-Man; Zhu, Li-Jing; Wang, Gang; Zeng, Zhi-Xiang
Abstract: Polyvinylidene fluoride (PVDF) membrane offers excellent potential for efficient separation and purification of O/W emulsions. However, oil-fouling presents a major obstacle to its further application. Herein, a strong underwater superoleophobic surface was engineered to efficiently inhibit oil-fouling. PVDF- graft -poly(2-(dimethylamino) ethyl methacrylate) (PVDF- g -PDMAEMA) membranes were first fabricated via vapor-induced phase separation (VIPS), in which the nascent liquid film was left in a vapor bath for a predesigned time ( t e ). The surface roughness increases by an order of magnitude when t e increases from 0 to 240 s, and the underwater oil contact angle (UWOCA) correspondingly increases to more than 150°. However, it declines with time gone until the oil droplets on the underwater membranes were swallowed up. After surface zwitterionicalization by the reaction between PDMAEMA and 1, 3-propane sulfonate, a strong underwater superoleophobic surface was obtained, even after being soaked in water for 24 h. It endows the zwitterionic membrane with superior crude oil/water emulsion separation (with a flux of 749.7 ± 44.8 L m −2 h −1 and separation efficiency of 99.4 ± 0.1%) and excellent oil-fouling resistance (with a flux recovery rate of more than 90%), improving the potential value of porous membranes in oily water treatment. Graphical Abstract: ga1 Highlight: PVDF-g-PDMAEMA membrane with high roughness was fabricated via VIPS. The membranes were efficiently subjected to surface zwitterionicalization by 1, 3-PS. The zwitterionic surfaces exhibited strong underwater superoleophobicity. The zwitterionic membranes efficiently separated oily water in high oil-fouling resistance.